Analysis of Science, Technology, and Innovation in Emerging Economies - Pardo Martínez, Clara Inés.; Cotte Poveda, Alexander; Fletscher Moreno, Sylvia Patricia; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book outlines a number of different perspectives on the relationship between science, technology, and innovation in emerging economies. In it, the authors explore the aforementioned relationship as a pillar of economic development, driving growth in emerging economies. Employing a collaborative and interdisciplinary approach, the authors work to determine the main related factors and outcomes of the relationship between science, technology, and innovation, ultimately seeking to guide public policies to enhance the welfare of the population of an emerging economy.
Chapter 1. Influence of Science, Technology, and Innovation on Urban Sustainability -- Chapter 2. Applying a New Methodology to Measure Investment in R&D and Science and Technology Activities: The Case of Colombia -- Chapter 3. Bioprospecting Model for a New Colombia Drug Discovery Initiative in the Pharmaceutical Industry -- Chapter 4. Patents for All: Descriptive and Content Analysis of an Open Access Dataset of Colombian Patents 1930-2000 -- Chapter 5. Open Access Policies in Science to Promote Science, Technology and Innovation in Emerging Economies. The Case of Colombia -- Chapter 6. The Inclusion of Ecuadorian Women in Scientific-Technological Fields -- Chapter 7. Effects of Expenditures in Science, Technology and R&D on Technical Change in Countries in Latin America and the Caribbean -- Chapter 8. Science, Technology and Water Access -- Chapter 9. The Ecuadorian Technological Scientific Policy in the Frame of "Buen Vivir" -- Chapter 10. Against All Odds: Scientific Education, Scientific Competencies and the Ideals of an Eudcated Country. Colombia 1995-2015 -- Chapter 11. III and IV National Survey of Perception in Science, Technology and Innovation: A Comparative Review for the Years 2012 and 2015 -- Chapter 12. Innovation, Entrepreneurship, and Technology-based Clusters in Emerging Economies. How can the Madrid Aerospace Cluster Reinforce the Mexican Aerospace Industry? -- Chapter 13. Strategies for Identification of Interdisciplinary Research Subjects: Approach, Tools and Opportunities for Sustainable Development of Agricultural Economies. - Chapter 14. An analysis of urban public policy regarding science, technology and innovation from the perceptions of stakeholders. A case study for a city of an emerging country.
Keywords: Science -- Social aspects; International economic integration; Globalization; Technological innovations; Science and Technology Studies; Emerging Markets and Globalization; Innovation and Technology Management